The life history of Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae) fed on larvae and pupae of Plutella xylostella (L.) (Lepidoptera: Plutellidae) - Nunes, Gilmar da Silva [UNESP] (2022)
Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae) is reported as a potential predator of Plutella xylostella (L) (Lepidoptera: Plutellidae). In this study, we aimed to investigate whether fourth instar larvae, 1 or 3-day-old pupae of P. xylostella are suitable food for the development and reproduction of E. annulipes. We evaluated the characteristics of the predation, development of each life stage, and reproduction of the predator, by comparing them with an artificial diet. The nymphs consumed larvae and pupae equally in the first instars, but, from the third to fifth, they consumed snore larvae over pupae. Both males and females consumed more larvae over pupae as well. The shortest developmental period of nymphs was observed on larvae at the fourth instar. Males and females presented lower longevity fed on 3-day-old pupae. The highest longevity and survival rate of adults were observed on an artificial diet. Pupae of P. xylostella at any age provided the highest weight for nymphs (fourth and fifth instar) and adults. One-day-old pupae provided the highest fecundity (480 eggs/female); however, the egg hatching rate was higher when the predator fed on fourth instar larvae. The net reproductive rate was higher on 1-day-old pupae (292.8), but the intrinsic rate of increase (0.03 day(-1)) and the finite rate of increase (1.034 day(-1)) were lower, and both mean generation time (143.4 days) and doubling time (20.6 days) were higher on artificial diet. This study shows that fourth instar larvae, 1- and 3-day-old pupae of P. xylostella can be suitable food for the development and reproduction of E. annulipes.